Helicase promotes replication re-initiation from an RNA transcript - Bo Sun (Nature Portfolio, 2018)
During DNA replication, replicative helicases play an essential role for DNA unwinding to occur. Here the authors find that bacteriophage T7 helicase is also involved in replication re-initiation by interacting with a non-replicating DNAP and increasing unwinding rate.